2010
DOI: 10.1589/jpts.22.447
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between and Absolute Rotation Angle, Anterior Weight Bearing, Range of Flexion and Extension Motion in Cervical Herniated Nucleus Pulposus

Abstract: Abstract.[Purpose] We attempted to examine the range of motion (rotation, flexion and extension) of the neck and forward head posture in patients with a cervical herniated nucleus pulposus (C-HNP) and in normal persons through radiometry; and examined the correlations between the ranges of these motions and C-HNP.[Subjects] The study subjects were 15 patients with C-HNP at level 5 or 6 (C5-6, (males=5, females=10) and 15 normal persons (males=5, females=10). [Methods] We analyzed the degree of cervical lordos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
3
5
0
Order By: Relevance
“…Ro et al conducted correlation analyses on C-HNP patients and their results indicate that as ARA decreases, AWB increases (r= -0.80): The results of our present study also showed a strong negative correlation (r= -0.70) in that as ARA decreased, AWB increased 11) . The fact that the results of the present study are similar to the results of the study by Ro et al even though the subjects of our study were not C-HNP patients indicates the severity of the stress imposed on the cervical spines of college students.…”
Section: Discussionsupporting
confidence: 72%
“…Ro et al conducted correlation analyses on C-HNP patients and their results indicate that as ARA decreases, AWB increases (r= -0.80): The results of our present study also showed a strong negative correlation (r= -0.70) in that as ARA decreased, AWB increased 11) . The fact that the results of the present study are similar to the results of the study by Ro et al even though the subjects of our study were not C-HNP patients indicates the severity of the stress imposed on the cervical spines of college students.…”
Section: Discussionsupporting
confidence: 72%
“…In the present study, a significantly decreased RFEM was found in the HNP compared with the control group. This finding is agreement with a previous study 15) showing remarkably reduced flexion and extension in patients with cervical HNP compared with normal subjects. This result may be due to an abnormal alignment of the cervical spine resulting from an increased forward head posture in patients with HNP 15) .…”
Section: Discussionsupporting
confidence: 94%
“…This finding is agreement with a previous study 15) showing remarkably reduced flexion and extension in patients with cervical HNP compared with normal subjects. This result may be due to an abnormal alignment of the cervical spine resulting from an increased forward head posture in patients with HNP 15) . Thermographic imaging has been found to be useful in the diagnosis of a variety of diseases including cancers (i.e., breast, skin, etc.…”
Section: Discussionsupporting
confidence: 94%
“…It has been reported that ARA and RFEM of patients with herniated nucleus pulposus (HNP), are remarkably decreased compared to normal persons 10) . However, in the present study, which evaluated normal young adults, as ARA increased, extension and RFEM also increased.…”
Section: Discussionmentioning
confidence: 99%